Individual-environment interactions in swimming: The smallest unit for analysing the emergence of coordination dynamics in performance? - Guignard, B.; Rouard, A.; Chollet, D.; Hart, J.; Davids, K.; Seifert, L. (Sports Medicine, 2017)
Displacement in competitive swimming is highly dependent on fluid characteristics, since athletes use these properties to propel themselves. It is essential for sport scientists and practitioners to clearly identify the interactions that emerge between each individual swimmer and properties of an aquatic environment. Traditionally, the two protagonists in these interactions have been studied separately. Determining the impact of each swimmer`s movements on fluid flow, and vice versa, is a major challenge. Classic biomechanical research approaches have focused on swimmers` actions, decomposing stroke characteristics for analysis, without exploring perturbations to fluid flows. Conversely, fluid mechanics research has sought to record fluid behaviours, isolated from the constraints of competitive swimming environments (e.g. analyses in two-dimensions, fluid flows passively studied on mannequins or robot effectors). With improvements in technology, however, recent investigations have focused on the emergent circular couplings between swimmers` movements and fluid dynamics. Here, we provide insights into concepts and tools that can explain these on-going dynamic interactions in competitive swimming within the theoretical framework of ecological dynamics.